INVESTIGATION OF THE IMPACT OF ELECTRIFYING TRANSPORT AND HEAT SECTORS ON THE UK DISTRIBUTION NETWORKS - Gan, Chin Kim (2011)
The work in this paper is conducted in collaboration with the Energy Networks Association to inform the current UK debate on the smart metering roll out programme in relation to the appropriate functionality of smart meters and corresponding requirements on communication infrastructure. The overall aim of the investigation is to estimate the order of magnitude benefits of future real-time distribution network control that incorporates real time demand response facilitated by smart metering infrastructure.